Essential Oil Composition of Endemic Arabis purpurea Sm. & Arabis cypria Holmboe (Brassicaceae) from Cyprus - Polatoglu, Kaan; Servi, Huseyin; Ozcinar, Ozge; Nalbantsoy, Ayse; Gucel, Salih (JAPAN OIL CHEMISTS SOC, 2017)
There are very few reports on the phytochemistry of the Arabis L. (Brassicaceae) species in the literature. Here we present essential oil composition of aerial parts of two endemic Arabis species from Cyprus. The essential oils of Arabis purpurea Sm. and Arabis cypria Holmboe afforded very low oil yields (< 0.01% (v/w) yield). Sixty six compounds were identified in the essential oil of A. purpurea that represent 82.75 +/- 0.21 % (n = 3) of the oil. The major components of the oil were nonacosane 16.18 +/- 0.13 %, heptacosane 14.91 +/- 0.17 %, hexahydrofarnesyl acetone 12.44 +/- 0.10 % and phytol 7.36 +/- 0.10 % (n = 3). Forty three compounds were identified in the essential oil of A. cypria which represent 81.28 +/- 1.55 % (n = 3) of the oil. The major components of the oil were nonacosane 20.25 +/- 0.47 %, heptacosane 9.13 +/- 1.88 %, hexahydrofarnesyl acetone 9.03 +/- 0.44 % and 1-tetradecanol 4.38 +/- 2.60 A) (n = 3). To the best of our knowledge this is the first report on the essential oil compositions of these species.
Keywords: Brassicaceae; Arabis purpurea Sm.; Arabis cypria Holmboe; nonacosane; hexhydrofarnesyl acetone; heptacosane; phytol; TANACETUM-CHILIOPHYLLUM FISCH; SCHULTZ BIP.; CHEMICAL-COMPOSITION; VAR. CHILIOPHYLLUM; VOLATILE COMPOUNDS; FLORAL SCENT; TURKEY; L.; CONSTITUENTS; GRIERSON; Chemistry; Food Science & Technology